(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article at maintaining the health of children today is one of the pressing problems of our time. A special place in the world education system is occupied by the education of preschool children, the expansion of mental capabilities, healthy and comprehensively mature adulthood, the physical education of preschool children in the general system of education and upbringing. It is as a result of the targeted pedagogical influence in preschool childhood that the Health, general endurance and ability to work, vital activity and other qualities necessary for the comprehensive harmonious development of the individual are formed. The formation of physical qualities, abilities and abilities of movement is closely related to the development of balancing agility, the upbringing of aesthetic feelings and moral-volitional personality traits. At the same time, physical education Control and correctional methods are indicated in preschool educational organizations.